Anatomía y química foliar en especies ornamentales de Arecaceae: Posibles barreras a la alimentación de Raoiella indica Hirst (Acari: Tenuipalpidae) - Vásquez, Carlos; Egurrola, Zurich; Valera, Rosario; Sanabria, María E.; Colmenárez, Yelitza [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2015)
The red palm mite, Raoiella indica Hirst (Acari: Tenuipalpidae), has been reported on 91 host plant species in Neotropical region. However, potential to feed on these plant species depends on anatomical and chemical characteristics, which can influence mite development and reproduction. Thus, in this study anatomical features such as cuticle-epidermis width, mesophyll depth and width, stomatal index and density; and also secondary metabolites (SM) concentration obtained by thin layer chromatography were evaluated as potential barriers to mite feeding in 11 ornamental important Arecaceae species Coccothrinax barbadensis (Lodd. ex Mart.) Becc., Cocos nucifera L, Mauritia flexuosa L. f., Roystonea oleracea (Jacq.) O.F. Cook, Sabal mauritiiformis (Karsten) Griseb. & Wendl, Syagrus amara (Jacq.) Mart., S. coronata (Martius) Becc., S. romanzoffiana (Cham.) Glassman, S. sancona H. Karsten, S. schizophylla (Mart.) Glassman and S. stenopetala Burret. Although differences in cuticle and depth mesophyll were detected, these variables seem not to represent a feeding barrier for R. indica feeding. Conversely, stomata disposition on leaf surface could make infra-capitulum and stylets easier to penetrate and feed. More detailed studies on anatomy and chemical composition of Arecaceae and Zingiberales species should be addressed to determine their effect on red palm mite´s development and reproduction.
Leaf anatomy and chemistry in ornamental Arecaceae species: Possible barriers to Raoiella indica Hirst (Acari: Tenuipalpidae) feeding
Keywords: Palms; Red palm mite; Secondary metabolites; Stomata